en - I Wayan Gede Candra Wibawa; I Made Netra; I Made Rajeg (Program Magister Linguistik Universitas Udayana, 2022)
This study is entitled â€œThe Translation of Taboo Words in the Deadpool 2 Movie Subtitleâ€. This study aimed at describing the types of taboo words found in the Deadpool 2 movie and analyzing the translation procedures applied in translating the taboo words from English subtitle text into Indonesian. The data sources of this study were the Deadpool 2 movie subtitle, both its English and Indonesian versions. The descriptive qualitative method was applied in analyzing the data. The taboo words were analyzed using Jayâ€™s theory about the types of taboo words. Meanwhile, the theory proposed by Vinay and Dalbernet was used to describe the translation procedure in translating taboo words into Indonesian. The results of the study show that not all types of taboo words and translation procedures were found. Through the analysis of taboo words obscenity was the most type of taboo word shown in the movie and there were only two translation procedures applied in translating the taboo words.